Effect of Self-Citation on H-Index: A Study of Top 1% Highly Cited Iranian Scientists in Medical Sciences - Naderbeigi, Farahnaz; Mokhtari, Heidar; Saberi, Mohammad Karim; Amiri, Mohammad Reza; Vakilimofrad, Hossein; Masoumi, Leyla (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2022)
Background: H-index is one of the main bibliometric indicators for evaluating researchers. It has been criticized due to the effect of self-citation rate on its increase. Aim: This study aimed at analyzing the state of top 1% highly-cited Iranian scientists in medical sciences in ESI for investigating the effect of their self-citations on their h-indices. Methods: Iranian Medical Science Scientometric Information Database, Essential Science IndicatorsTM (ESI) and Scopus indexing/abstracting database were used for data extraction. Data analysis was conducted in Excel and SPSS.. Results: In total, 6.15% of citations were self-citations that resulted in increase in h-index by 2.49 units. After excluding self-citations, the h-indexes of 23.4% of the studied scientists did not change and the mean rate of h-index decreased by 2.49. A correlational test showed the strong correlation between self-citation count and h-index rate (r=.718). Conclusion: Self-citation is present as a common phenomenon in all scientific communities and increases in h-index. If not used for manipulating bibliometric indicators, it can make the scientific works more visible for potential readers and consequently receiving more citations.